Decision-making in orthopedic and regional anesthesiology a case-based approach - Anderson, Michael R. 1981-; Rosenblatt, Meg A.; Wilson, Sylvia H. (Cambridge University Press, 2015)
In light of evolving techniques and strategies for increasingly complex orthopedic procedures, this accessible guide to patient management outlines the considerations involved in selecting the most suitable anesthetic for both common and complex clinical scenarios. Chapters cover a multitude of clinical presentations and procedures, ranging from orthopedic trauma to total joint replacement, outpatient hand procedures and regional anesthetic placement in patients with pre-existing conditions. Each chapter discusses and evaluates multiple approaches, accompanied by a review of the current literature. Abundant case scenarios of patients undergoing orthopedic surgical or regional anesthesia provide a handy framework for specialists and consultants, as well as an invaluable guide for trainees in anesthesia, regional anesthesia and emergency medicine.